Effects of Crystal Quality and Morphology on the Mechanical Performance of LLM‐105 Based PBXs. Issue 10 (14th August 2019) - Yang, Zhijian; Lin, Congmei; Gong, Feiyan; Zeng, Chengcheng; Zhang, Jianhu; Huang, Fenglei
Abstract: Mechanical performance is significant for the application of pressed polymer bonded explosives (PBXs) materials. In this research, several types of 2, 6‐diamino‐3, 5‐dinitropyrazine‐1‐oxide (LLM‐105) were selected to study the effects of crystal quality and morphology on the mechanical performance of LLM‐105 based PBXs. The surface bonding status of the LLM‐105 crystal and molding powder was characterized by scanning electron microscopy (SEM) and contact angle analysis, and the moldability was evaluated by determining the relative density of pressed cylinders of corresponding PBXs. Besides, static and dynamic mechanical properties were studied and compared, presenting the compressive, tensile and creep curves. For LLM‐105 based PBXs, spherical morphology and rough surface could result improved mechanical strength and creep resistance, facilitating the structural and dimensional stability of charges. In this case, it can bring benefits for their reliability and safety performances during application. Abstract :